To The Problem of Law-Making Errors: A General Theoretical Aspect - Vladimir Valentinovich Kozhevnikov; Muhammad Ridwan (Polit Journal Scientific Journal of Politics, 2025)
The article examines the problems of law-making legal errors. Particular attention is paid to the subjective side of the law-making error, as well as the legal consequences of their commission. The article also draws attention to the consequences of law-making errors that affect the interests of the population, causing corruption and disrespect for the law. From the author's point of view, law-making errors should be differentiated from doctrinal (conceptual) errors.